STRATEGI MANAJEMEN RISIKO DAN TRANSPARANSI DALAM OPTIMALISASI PENGELOLAAN WAKAF UANG DIGITAL - Ainur Rohmah; Nani Hanifah (Universitas KH. Mukhtar Syafaat, 2025)
Digital cash waqf in Indonesia has great potential but low realization due to a public trust crisis caused by weak risk management and lack of transparency. This study aims to formulate a conceptual model integrating risk management and transparency strategies. Using a Systematic Literature Review (SLR) method based on PRISMA from 2020–2026 journals, five main risks were identified: operational, fund distribution, legal & sharia compliance, financial, and cyber. Mitigation strategies include diversification, cybersecurity, blockchain, regulatory compliance, and contingency planning. Transparency is implemented through three pillars: pre-transaction, transaction, and post-transaction. The integrated model of risk management, transparency, and good governance is key to optimization. The study concludes that optimizing digital cash waqf requires simultaneous integration supported by consistent regulation and improved digital literacy.